2012
DOI: 10.1007/s00216-012-6495-4
|View full text |Cite
|
Sign up to set email alerts
|

Identifying indoor environmental patterns from bioaerosol material using HPLC

Abstract: A substantial portion of the atmospheric particle budget is of biological origin (human and animal dander, plant and insect debris, etc.). These bioaerosols can be considered information-rich packets of biochemical data specific to the organism of origin. In this study, bioaerosol samples from various indoor environments were analyzed to create identifiable patterns attributable to a source level of occupation. Air samples were collected from environments representative of human high-traffic and low-traffic in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…It has been recognized that ambient air is composed of a "protein soup" containing bacteria, viruses, spores, pollen, and a slew of biological debris from humans, animals, insects, and plants all ranging in size from a few nanometers to roughly 100 microns. To date most research examining bioaerosols has concentrated on either indoor environments or atmospheric studies (Kang et al, 2012;Schneider et al, 2011;Staton et al, 2013). These studies have focused on determining local air quality, possible pathogenic transmission of aerobacteria and viruses, bioaerosol output of particular locations such as a trash dump, or the effects of large scale fires (Alvarez et al, 1995;Costa et al, 2012;Menetrez et al, 2009;Rogers et al, 1991).…”
Section: Introductionmentioning
confidence: 98%
“…It has been recognized that ambient air is composed of a "protein soup" containing bacteria, viruses, spores, pollen, and a slew of biological debris from humans, animals, insects, and plants all ranging in size from a few nanometers to roughly 100 microns. To date most research examining bioaerosols has concentrated on either indoor environments or atmospheric studies (Kang et al, 2012;Schneider et al, 2011;Staton et al, 2013). These studies have focused on determining local air quality, possible pathogenic transmission of aerobacteria and viruses, bioaerosol output of particular locations such as a trash dump, or the effects of large scale fires (Alvarez et al, 1995;Costa et al, 2012;Menetrez et al, 2009;Rogers et al, 1991).…”
Section: Introductionmentioning
confidence: 98%
“…8 One of the main factors affecting the indoor dust composition is a human attendance. 15 The presence of skin flakes in the indoor environment has been assessed using microscopy, 16 HPLC, 17 size-resolved fluorescence measurements, 10 and gene sequencing of dust samples. 9 There are numerous lines of evidence indicating that human skin flakes are a major component of settled house dust and bioaerosol particles presented in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…PBAs have a dimension ranging between 0.3 and 100 µm and they contain a large variety of different biomolecules, such as lipids, nucleic acids, amino acids, and glycosylates. Recently, it has been found that proteins compose a much larger portion of the atmospheric particle budget than the trace amount previously assumed, with potentially up to 25% of atmospheric particles having a biological origin …”
Section: Introductionmentioning
confidence: 98%
“…Recently, it has been found that proteins compose a much larger portion of the atmospheric particle budget than the trace amount previously assumed, with potentially up to 25% of atmospheric particles having a biological origin. [2] Concerning atmospheric proteins, it has been recognized that outdoor environment is composed of a "protein soup" containing bacteria, fungi, spores, house dust mites, multiple pollens, animal dander, molds, and fragments of animals, insects, and plants which are implicated in severe lung diseases, causing respiratory disorders, asthma, and chronic obstructive pulmonary disease to exposed individuals. [3,4] Due to the difficulty of specifically tracing these microorganisms in air, there is lack of knowledge about the dispersal of airborne microorganisms even though it is well recognized that an exposition to a complex mixture of toxins and allergens can lead to respiratory tract infections.…”
Section: Introductionmentioning
confidence: 99%